Differences in negativity bias probably underlie variation in attitudes toward change generally, not political ideology specifically. Issue 3 (27th June 2014) - Ludeke, Steven G.; DeYoung, Colin G.
Abstract: Many of the characteristics cited in Hibbing et al.'s account are ineffective predictors of economic conservatism. However, these same characteristics are often associated with differences not only in social conservatism but also in religiousness and authoritarianism. Hibbing et al. may have offered a useful explanation of traditionalism and attitudes toward change across domains rather than of general political attitudes.